The Use of Artificial Intelligence Innovation in Islamic Religious Education - Rafiqah Dwi Rahmah; Tasman Hamami; Sukiman Sukiman (Yayasan Keluarga Guru Mandiri, 2025)
The pervasive integration of artificial intelligence (AI) necessitates continuous human innovation and adaptation to ensure the societal relevance of AI. Within education, particularly in Islamic Religious Education (IRE), leveraging AI is crucial for modernizing learning approaches. This study critically examines the application of AI innovations in IRE, specifically when they diverge from the core principles of literacy. Employing a systematic literature review, we meticulously gathered articles from Scopus and Google Scholar using Publish or Perish, subsequently screening and analyzing them according to the PRISMA 2020 guidelines. This process yielded 28 relevant articles for review. The findings suggest that the sustained and consistent use of AI in IRE learning environments may potentially undermine human critical thinking skills. Consequently, fostering habits of reading and engaging in robust discussions emerges as a vital solution to preserve and enhance individual cognitive abilities. This research contributes comprehensive insights into the utilization of AI innovations in IRE pedagogy over the past five years, offering a timely critique and guiding future educational practices.